A stitch in time saves sight: Craniopharyngioma - Suryawanshi, Sneha; Kanhere, Sujata (Indian Journal of Case Reports, 2020)
Craniopharyngiomas are rare dysontogenic, extra-axial, slow-growing tumors arising from the remnants of the Rathke’s pouch and located within the sellar or parasellar region, which can be solid, cystic, or calcified. We are reporting a case of an 11-year-old female child who presented with complaints of sudden onset rapid diminution of vision in the right eye more than the left eye for 2 months, for distant and near vision, with normal visual fields. The patient was diagnosed as having craniopharyngioma based on magnetic resonance imaging. Surgery was done without delay, restoring her vision. Histopathology of tumor confirmed the diagnosis. This case highlights the fact that immediate neuroimaging in children presenting with sudden onset, rapidly progressive vision loss helps in early diagnosis and management of craniopharyngioma and to retrieve lost vision.